POTENSI PARIWISATA DALAM PEMBERDAYAAN MASYARAKAT DI PULAU BELIMBING KECAMATAN KUOK KABUPATEN KAMPAR - Fiqri Syahwidi Saputra; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In a study using this descriptive qualitative research method, there is a goal to know how the Tourism Potential in Community Empowerment in Belimbing Island District Kuok Kampar District. In addition, this study also describes the potential of the island of belimbing, describing the role of tourism in community empowerment. Based on the results of research that has been done there are results showing the Potential Village Tourism Island Belimbing has attractions that are Nature and Culture attractions. Nature Attraction is River, Plantation, Orange, Guava Citra Keramba (floating net cages), Rice fields. While Cultural Attractions there Pangkal Barge, Manggelek Tobu, Orphans Benefit, Balimau Kasai, Calempong, Silat Dance. Tourism that grows in the middle of the island community is very good for improving the economy and income of its own people, and to promote the island of starfruit as Tourism Village, In general tourism, concerned in the citrus and jambu Citra plantation economy. Local cultural traditions such as Manggelek Tobu, Balimau Kasai, Bakela, Pangkal Tongkang. Keywords: Potential, Tourism, Empowerment, Society